2023
DOI: 10.3847/psj/acaddb
|View full text |Cite
|
Sign up to set email alerts
|

Highly Resolved Topography and Illumination at Mercury’s South Pole from MESSENGER MDIS NAC

Abstract: Mercury’s south polar region is of particular interest since Arecibo radar measurements show many high-reflectance regions consistent with ice deposits. However, current elevation information in Mercury’s southern hemisphere is not sufficient to perform detailed modeling of the illumination and thermal conditions at these radar-bright locations and to constrain properties of the volatiles potentially residing there. In this work, we leverage previously existing elevation maps of Mercury’s surface from stereo-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Despite the strong attraction for constructing higher resolution 3D products without stereo coverage, the validity of 3D reconstruction based on deep learning for planetary research should be carefully investigated before the use of scientific applications, as the referencing of a height plane highly depends on the ground-truth employed, such as LiDAR and stereo DEM and no guarantee to inherit their accuracy into the dimension of far finer resolution. In the case of shape from shading, the validation of products is also strongly required, even with recent successes in extensive 3D reconstruction, as shown in Mercury by Tenthoff et al [226] and Bertone et al [227]. It's because the establishment of a fully working reflectance function on the planetary surface as well as the solution of geodetic control in a single image source are not yet available.…”
Section: Ckmentioning
confidence: 99%
“…Despite the strong attraction for constructing higher resolution 3D products without stereo coverage, the validity of 3D reconstruction based on deep learning for planetary research should be carefully investigated before the use of scientific applications, as the referencing of a height plane highly depends on the ground-truth employed, such as LiDAR and stereo DEM and no guarantee to inherit their accuracy into the dimension of far finer resolution. In the case of shape from shading, the validation of products is also strongly required, even with recent successes in extensive 3D reconstruction, as shown in Mercury by Tenthoff et al [226] and Bertone et al [227]. It's because the establishment of a fully working reflectance function on the planetary surface as well as the solution of geodetic control in a single image source are not yet available.…”
Section: Ckmentioning
confidence: 99%
“…The Mercury Dual Imaging System (MDIS) captured multispectral images of Mercuryʼs surface, and the Mercury Laser Altimeter (MLA) measured the northern hemisphere topography (Solomon & Anderson 2018). These measurements enabled the derivation of maps of shadowed regions, which showed a considerable overlap with the radar-bright deposits near both poles (Deutsch et al 2016;Chabot et al 2018b;Barker et al 2022;Gläser & Oberst 2022;Bertone et al 2023). Modeling of the thermal conditions using the MLA-determined topography at Mer-curyʼs north polar region revealed that water ice was stable over geologic timescales within many of the permanently shadowed regions (PSRs; Paige et al 2013;Chabot et al 2018a).…”
Section: Introductionmentioning
confidence: 99%